2013
DOI: 10.1016/j.bbagen.2013.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Decreased reticuloendothelial system clearance and increased blood half-life and immune cell labeling for nano- and micron-sized superparamagnetic iron-oxide particles upon pre-treatment with Intralipid

Abstract: Background Superparamagnetic iron-oxide nanoparticles are useful as contrast agents for anatomical, functional and cellular MRI, drug delivery agents, and diagnositic biosensors. Nanoparticles are generally cleared by the reticuloendothelial system (RES), in particular taken up by Kupffer cells in the liver, limiting particle bioavailability and in-vivo applications. Strategies that decrease the RES clearance and prolong the circulation residence time of particles can improve the in-vivo targeting efficiency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 52 publications
(75 reference statements)
0
46
1
Order By: Relevance
“…S4D), but the in silico model demonstrated that increased liver concentrations are expected (Fig. S4E) without invoking other factors that contribute to the liver-uptake of Intralipid® [40]. Subsequent to increasing liver concentrations, ILE treatment increased excretion of radiolabel into the urine by 10 minutes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S4D), but the in silico model demonstrated that increased liver concentrations are expected (Fig. S4E) without invoking other factors that contribute to the liver-uptake of Intralipid® [40]. Subsequent to increasing liver concentrations, ILE treatment increased excretion of radiolabel into the urine by 10 minutes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the role of metabolism, the increased liver bupivacaine concentrations could not be accounted for by a flow effect but the in silico models demonstrated that invocation of reticulo-endothelial cell uptake was not needed to increase liver concentrations. The reticulo-endothelial system might be playing a role in uptake of the ILE [40], but we did not specifically test for this. Also, we tested the effect of inhibiting CYP3A4, the main metabolizer of bupivacaine, but bupivacaine is also processed in small amounts by other CYP's indicating that tests with other inhibitors might yield more information.…”
Section: Discussionmentioning
confidence: 99%
“…In general, Iron-oxide-particles have short blood half-life, depending on their size and surface coating materials [17]. We have shown [54] that the pre-treatment of Intralipid ® prior to iron-oxide particle administration can temporarily inhibit Kupper cells in the liver, increase its blood half-life, thus, improve labeling efficiency. For the present study, MPIO was given 1-to-3 days prior to the ischemic surgery.…”
Section: Discussionmentioning
confidence: 98%
“…The standard-size nanoparticles are composed of ferric (Fe 3þ ) and ferrous (Fe 2þ ) iron (Wahajuddin and Arora, 2012). They have been trapped in the reticuloendothelial system through endocytosis or phagocytosis to explore their cytotoxicity profile due to the dissolving capacity of iron oxide under acidic conditions Liu et al, 2013a). In addition, Fe 3þ ions can be stored in adult humans, accumulating up to 3e5 g of iron.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%